Development and Validation of a Test of Science Process Skills for Secondary Students on Cellular Living System Organization Matter: Rasch Model Analysis - Sigit Subagja; Bibin Rubini; Surti Kurniasih (Postgraduate, University of Mataram, 2023)
This study aims to develop and implement the instrument of science process skills tests on cellular living system organization matter, explicitly designed for secondary students. The indicators developed include formulating hypotheses, communicating, applying concepts, asking questions, observing, planning experiments, using laboratory tools, classifying, and interpreting data. The steps of this research are theoretical construction, determining the purpose of the assessment, constructing indicator items, compiling the items, expert judgment, instrument revision, field trials, and finalization of the instrument. The Science Process skills test consisted of 27 multiple-choice questions. The subject was 30 secondary school students. Data were analyzed using Rasch analysis. Evidence of the validity and reliability of the tests are presented. The conclusion is that the science process skills test instrument is theoretically and empirically valid and reliable